Exploring the performance limiting parameters of perovskite solar cell through experimental analysis and device simulation. (December 2015) - Yadav, Pankaj; Pandey, Kavita; Bhatt, Parth; Raval, Dhyey; Tripathi, Brijesh; Kanth P., Chandra; Pandey, Manoj Kumar; Kumar, Manoj
Highlights: Potentially low-cost production architecture of perovskite solar cells. Perovskite cell as a heterojunction for excitation and dissociation of charge carriers. Use of a diode model to explore junction characteristics. SCAPS simulation is done to explore the role of interface defects and band offsets. Abstract: A perovskite heterojunction solar cell is fabricated with architecture of hole transport material (HTM) free discrete electrode. The morphological, structural and optical properties are studied by FESEM, XRD and UV–Vis spectrophotometry techniques. A single diode model has been used to investigate the cell characteristics. The interface between TiO2 and CH3 NH3 PbI3 layer is found analogous to Schottky diode that acts as a heterojunction for excitation and dissociation of charge carriers due to the existence of an internal electric field at the junction. The SCAPS simulation is done to explore the role of interface defects and band offsets. Device simulation has shown an improvement of 16%, 6% and 25% in V OC, FF and η respectively with incorporation of the HTM layer in device structure.